Effect of broccoli extract supplement on carcass traits and lipid metabolism in Holstein steers - Chen, Shuangshuang; Zhang, Xinyu; Zhu, Tao; Tang, Die; Wen, Mingxing; Tang, Chuang; Hou, Ling; Zeng, Zhiyao; Tong, Shanfeng; Li, Xuelong; Lu, Lu; Long, Keren; et al. (Frontiers in Genetics, 2025)
IntroductionFeed additives are widely used to enhance feed efficiency and promote animal growth and health. Broccoli extract, a plant-derived additive rich in bioactive compounds, has potential physiological regulatory effects. However, its specific impact on cattle remains unclear.MethodsThis study investigated the effects of broccoli extract supplementation on growth performance, rumen microbial composition, blood metabolites, and gene expression in the liver and adipose tissue of castrated Holstein bulls. Animals were randomly assigned to three groups and supplemented daily with 0 g, 15 g, or 18 g of broccoli extract for 45 days.ResultsNo significant differences were observed among groups in average daily gain, dressing percentage, or fecal score (P > 0.05). However, broccoli extract supplementation significantly improved feed intake, lying time, rumination rate, and net meat yield, while reducing subcutaneous fat percentage (P < 0.05). 16S rRNA sequencing revealed increased rumen microbial diversity in the 18 g group. Blood metabolomics showed elevated prostaglandin E2 levels and enrichment in pathways related to inflammation and lipid metabolism. Transcriptomic analysis revealed enrichment of pathways associated with immune responses and lipid regulation. Integrated multi-omics analysis further demonstrated strong correlations between lipid-related metabolites and gene expression patterns.ConclusionBroccoli extract supplementation modulated feeding behavior and rumen microbiota, improved carcass traits, and influenced lipid metabolism and inflammation-related pathways in Holstein cattle. These findings highlight its potential as a functional feed additive for improving beef cattle production.